Fibroblast growth factor 23 modifies the pharmacological effects of angiotensin receptor blockade in experimental renal fibrosis. Issue 1 (24th May 2016) - de Jong, Maarten A.; Mirkovic, Katarina; Mencke, Rik; Hoenderop, Joost G.; Bindels, René J.; Vervloet, Marc G.; Hillebrands, Jan-Luuk; van den Born, Jacob; Navis, Gerjan; de Borst, Martin H.; ,
Abstract : Background. Blockade of the renin–angiotensin–aldosterone system (RAAS) retards progression of chronic kidney disease. Yet, in many patients, the renoprotective effect is incomplete. A high circulating level of the phosphaturic hormone fibroblast growth factor 23 is associated with an impaired response to RAAS blockade–based therapy in clinical studies. Therefore, we addressed whether administration of recombinant fibroblast growth factor 23 (FGF23) interferes with the efficacy of angiotensin receptor blocker (ARB) treatment in a mouse model of renal fibrosis [unilateral ureteral obstruction (UUO)]. Methods. UUO mice were treated with losartan (100 mg/L in drinking water), recombinant FGF23 (160 ng/kg i.p. twice daily), their combination or vehicle ( n = 10 per group). Seven days after the UUO procedure, kidney tissue was analyzed for markers of RAAS activity, inflammation and fibrosis using real-time PCR and immunohistochemistry. Results. In the contralateral (non-affected) kidneys of ARB-treated UUO mice, administration of FGF23 reversed the induction of renin, ACE, ACE2 and AT1 receptor mRNA expression, suggesting interference with the physiological response to RAAS blockade by FGF23. Furthermore, recombinant FGF23 infusion prevented ARB-induced klotho upregulation in contralateral kidneys. In the UUO kidneys, klotho was majorly reduced in all groups. Pro-inflammatory gene expression (MCP-1, TNF-α) induced in UUO kidneys was reduced by ARB treatment; this anti-inflammatory effect was reversed by FGF23. In contrast, ARB-induced reduction of (pre-)fibrotic gene expression was not reversed by FGF23. Conclusions. Our findings show pharmacological interaction between exogenous FGF23 and losartan, thus serving as a proof of principle for crosstalk between the FGF23–klotho axis and RAAS.